Nimrod Muhumuza, Children’s rights and climate action: Assessing the suitability of South Africa’s domestic normative framework (Prawa dzieci a działania klimatyczne. Ocena adekwatności krajowych ram normatywnych Republiki Południowej Afryki), „African Hu - Dąbrowska, Anna (Studia Prawa Publicznego, 2026)
Nimrod Muhumuza, Children’s rights and climate action: Assessing the suitability of South Africa’s domestic normative framework (Prawa dzieci a działania klimatyczne. Ocena adekwatności krajowych ram normatywnych Republiki Południowej Afryki), „African Human Rights Law Journal” 2026, vol. 26, no. 1, s. 1–33, https://www.ahrlj.up.ac.za/muhumuza-n